Pulp revascularization in teeth with incomplete rhizogenesis: literature review (Research, Society and Development, 2022)
In the context of endodontic treatment, incomplete rhizogenesis presents a great challenge for dentists. In these cases, there is a technical limitation, because teeth in this condition has channels with thin walls, which makes mechanical instrumentation difficult due to the risk of fractures. Build a consistent view of the applicability of the revascularization technique in the treatment of necrotic teeth with incomplete rhizogenesis, through a literature review. It consists of a literature review in the databases: Bireme, SciELO, PubMed/medline, LILACS. The descriptors Pulp revascularization, incomplete rhizogenesis, Endodontics, Regenerating endodontics, irrigating solutions were used. 400 articles were found, among them 376 publications were excluded for not showing relevant and specific information on the subject of this study, and 24 studies were selected. Revascularization is a procedure more likely to be performed in current times, and can be defined as the invagination of indifferent cells in the apical region of teeth with an open apex. Given the present study, it was analyzed that pulp revascularization is a treatment with a consistent clinical outcome, demonstrating an increase in root thickness and length as well as continuous development and apical closure.